Protesa Maksilo Fasial Kerangka Logam Kombinasi Bahan Termoplastik pada Defek Kelas II Aramany Pasca Hemimaxillectomy - Yuyus Mohamad Ilyas Djunaedy (Faculty of Dentistry, Universitas Gadjah Mada, 2012)
Background: Hemimaxilectomy surgery may cause facial defects, impaired function of speech, swallowing, mastication, esthetics as well as psychiatric patients and can cause problems I rehabilitation. Objective: This case report aims to determine the effect of maxillofacial prosthesis using ametal frame combination of thermoplastic materials in class II defects aramany to the aesthetic, retention, and stabilization of the prosthesis. Case: a 58- year old woman has done hemimaxilectomy, since ayear ago. Defective class II aramany, most of the maxillary teeth are gone, the teeth are still there 11, 13 and 17. Taking impression using hidrocoloid irreversible material was done following subjective, objective and radiographic examination, then the processs of ametal frame, MMR, teeth arrangement, wax denture try in, then do the lab thermoplastic material, and insertion of the prosthesis. Manufacture of metal framework prosthesis combination of thermoplastic materials of class II defects aramany is the right choice. Conclusion: it can result in the retention, stabilization, good occlusion and esthetics.